The Service of Bungus Ocean Fishery Port to Support Tuna Industries - Zainal, Resti; Nofrizal, Nofrizal; Isnaniah, Isnaniah (Journal of Coastal and Ocean Sciences, 2023)
The services of the Bungus Ocean Fishery Port as the only tuna Fishery port in West Sumatra in supporting the availability of facilities required by each tuna industry stakeholder. The purpose of this study is to determine the services from the Bungus Oceaning Fishery Port that are currently being experienced by fisheries stakeholders, especially tuna and to determine the level of satisfaction of tuna entrepreneurs with the performance of the Bungus Ocean Fishery Port. The data analysis used is weighting or scoring, and then IPA and CSI analysis is carried out. The results showed that the Bungus Ocean Fishery Port played a good role in providing production activities, infrastructure and public services, and tuna stakeholders felt quite satisfied with the performance of the Bungus Ocean Fishery Port in supporting the tuna industry